THE INFLUENCE OF PEEL EXTRACT MUSA PARADISIACA FORMATYPICA AGAINST KIDNEY HISTOLOGY, UREUM LEVELS AND CREATININ RATTUS NOVERGICUS AFTER INTENSIVE EXERCISE - Astawibawa, Putu Oky; Suarsana, I Nyoman; Suartini, I Gusti Ayu Agung (Buletin Veteriner Udayana; Vol. 14 No. 5 October 2022DO - 10.24843/bulvet.2022.v14.i05.p18, 2022)
Excessive physical activity triggers the formation of reactive oxygen species (ROS) that can damage the kidneys and other organs. This study aims to determine the effect of banana’s Kepok peel extract on the urea, creatinine, and renal histology levels of rats after intensive training. This study used 27 male white rats weighing 200-225 g. Rats were divided into three treatment groups: control (T0), intensive training (T1), intensive training (T2), and banana’s Kepok peel extract was given for 28 days. Urea samples were analyzed using the Urea Col method and creatinine samples were analyzed using the Jaffe method, while kidney samples were examined using histological preparations using the hematoxylin eosin (HE) staining method. In treatment with T0, urea and creatinine levels of 89,456 ± 2,938 and 0.867 ± 0.07 mg / dl were obtained, respectively; Treatment T1 with urea and creatinine levels 101,144 ± 1,805 and 0.944 ± 0.10 mg / dl, and treatment T2 with levels of urea and creatinine were 99,889 ± 4,075 and 0.900 ± 0.00 mg / dl, respectively. Observation of renal histology at T1 found degeneration and necrosis. T2 shows a decrease in degeneration and necrosis accompanied by an increase in regeneration of the epithelium of proximal and distal tubular cells. Supply of banana’s Kepok peel extract using a dose of 1 cc / kg bw. Urea levels in the T1 and T2 treatment groups differed significantly from T0, but when viewed from the mean standard deviation, it showed that T2 was approaching T0 levels. Creatinine T2 levels were not different from T0 and T1, while T0 was different from T1. Additionally, banana’s Kepok peel extract can prevent damage to kidney tissue but has not been significantly different.